Systematic analysis of cutting-edge technology for the wellbeing and safety of older persons - Ahmed Elsheikh (452015) (2025)
With global populations aging at an unprecedented pace, health and social care systems face mounting challenges in supporting older adults to live safely and independently. A wide range of assistive and digital technologies has emerged to enhance well-being, autonomy, and safety in later life. This systematic review explores the current landscape of such technologies, critically assessing their reported benefits, usability and implementation barriers. A structured search was conducted across six major databases for peer-reviewed studies published between January 2015 and May 2025. The review followed PRISMA 2020 guidelines, and methodological quality was assessed using the Mixed Methods Appraisal Tool (MMAT) (2018), augmented with technology-specific criteria. Of the 1838 records screened, 69 studies met the inclusion criteria. These studies evaluated interventions such as smart home systems, wearable health monitors, socially assistive robots and artificial intelligence (AI)-driven behaviour recognition tools. Reported outcomes included improved fall prevention, more rapid emergency response, increased engagement in daily activities and enhanced emotional well-being. Despite these promising results, many studies reported persistent challenges related to usability, affordability, data privacy and the mismatch between design and user needs. Only 17.4% of the studies included achieved high methodological quality. The findings highlight a need for more robust, user-centred research and the development of implementation models that account for the diversity of older adults’ needs. This review provides actionable insights for researchers, clinicians and developers aiming to design effective, equitable, and scalable technological interventions in rehabilitation and aging. Other Information Published in: Disability and Rehabilitation: Assistive Technology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/17483107.2025.2559185